+0  
 
0
158
2
avatar+1117 

Solve for y and x using the substitution method.

 

y = 2x 

 

y = 3x + 1

 Apr 29, 2019
edited by SmartMathMan  Apr 29, 2019
edited by SmartMathMan  Apr 29, 2019
edited by SmartMathMan  Apr 29, 2019
 #1
avatar
+1

 

y = 2x 

 

y = 3x + 1

 

I'm not certain what you're asking.  Solve for x?  Just set the two expressions equal.

 

                                                 3x + 1 = 2x

Subtract 2x from each side       3x – 2x + 1 = 2x – 2x

                                                   x + 1 = 0

Subtract 1 from each side           x + 1 – 1 = 0 – 1

                                                    x = –1

x = –1

 Apr 29, 2019
 #2
avatar+106539 
+1

The guest has used the substitution method.....

 

And since  x  = -1

 

Then y  =  2(-1)  =  - 2

 

cool cool cool

 Apr 29, 2019

35 Online Users

avatar
avatar